Deuteronomion : A Commentary Based on the Text of Codex Alexandrinus - Mohrmann, Douglas C. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
This commentary on Deuteronomion is based on Codex Alexandrinus, the single best complete witness to the Old Greek. It features a new transcription of the manuscript with a fresh translation that treats Deuteronomion as a sacred text that would have been read, studied, and cherished in a worshipping community. Notations of important variants with the other key manuscripts, such as p848, p963, and B (Vaticanus), appear regularly. This commentary represents an interpretative adventure, intentionally giving room for varied ancient reader-responses, and accordingly it functions within several literary spaces. First, it recognizes the substantial intratextual features between the book's narrative framing and its legal materials. Deuteronomion is also read in its hypotextual relation with the Pentateuch's other narratives and legal materials, chiefly within Exodus, Leviticus, and Numbers. Sensitivity to the Greek linguistic climate, the so-called koine Greek, is another space. Finally, and most distinctively, this commentary adds to its reading the many voices who read and used Deuteronomy, in either Hebrew or Greek forms, from the late Second Temple Period.